The professional development activities among the secondary school english teachers in Kuala Terengganu / Ruzana Omar, Faizah Mohamad and Nor Jawanees Ahmad Hanafiah - Omar, Ruzana; Mohamad, Faizah; Ahmad Hanafiah, Nor Jawanees (2013)
Annually, the English teachers attend various courses, workshops and programmes organized by District Education Department (PPD) and State Education Department (JPN). Though these teachers have attended the programmes for a number of years, very little research has been done to study the teachers' intentions to participate in professional development activities and the effectiveness of the programmes on the teachers. Thus, the present study was conducted to investigate the factors which influenced the in-service English teachers to involve in professional development activities and their perceptions on the programmes. A survey research was adopted and 40 sets of questionnaire were randomly distributed to 40 secondary school English teachers in Kuala Terengganu. The findings revealed that "Enhancing Knowledge in English" was the main factor which motivated the teachers to involve themselves in professional development activities and that personal gains did not play a significant role in determining the intention to involve in professional development activities. This study concludes that the teachers have positive responses towards the professional development activities they attended as the activities help to increase their knowledge and contribute new ideas for teaching the language.